Conductometría con el localizador apical electrónico propex pixi y el localizador apical YS-RZ-A - Trindade Gayoso, Caroline (2022)
The purpose of this research work was to compare the conductometrics with the Propex Pixi electronic apical locator and the YS-RZ-A apical locator. The type of research was quantitative, quasi-experimental design, comparative descriptive, cross-sectional. The sample consisted of 20 premolar teeth. The results that stood out the most were: The average of the measurements of the conductometrics with Propex Pixi was 17.68 mm. The mean of the conductometric measurements with YS-RZ-A was 17.50 mm. The most frequent conductometry with LAE Propex Pixi was 16.00 mm; followed by 19.50mm. The most frequent conductometry with LAE YS-RZ-A was 17.00 mm; 18.00mm and 19.00mm. The average measurement at the apical foramen with LAE Propex Pixi was 18.68 mm and at the anatomical foramen it was 19.10 mm. The average measurement at the apical foramen with LAE YS-RZ-A was 18.50 mm and at the anatomical foramen it was 19.10 mm. In none of the cases did the Electronic Apical Locators exceed the apical foramen. There is a significant difference between the measurement at the apical foramen with the LAE Propex Pixi and the anatomical apical foramen (p=0.000). There is a significant difference between the measurement at the apical foramen with the LAE YS-RZ-A and the anatomical apical foramen (p=0.000). There are no significant differences between the conductometrics obtained with LAE Propex Pixi and YS-RZ-A (p=0.763).